Transcriptional Profiling Reveals the Regulatory Role of CXCL8 in Promoting Colorectal Cancer - Li, Jie; Liu, Qin; Huang, Xuan; Cai, Yurui; Song, Li; Xie, Qianrong; Liu, Fuchuan; Chen, Xiaochun; Xu, Peng; Zeng, Fanwei; Chu, Yanpeng; Zeng, Fanxin (Frontiers in Genetics, 2020)
As a member of the CXC chemokine family, C-X-C motif chemokine ligand 8 (CXCL8) is involved in tumor proliferation, migration and invasion. However, CXCL8 function in colorectal cancer (CRC) is still controversial. Here, we analyzed RNA-sequencing data for screening differentially expressed genes and pathways through Gene Ontology (GO) enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway in CRC. CXCL8 was significantly increased in early and advanced stages, as well as metastasis and non-metastasis at mRNA level in 91 CRC cases using RNA-sequencing data. Moreover, these findings were also confirmed at protein level in 87 CRC cases by immunohistochemistry assays. Protein-protein interaction (PPI) prediction combined with the transcriptional profiling revealed that CXCL8 positively correlated cAMP responsive element binding protein 1 (CREB1)/ribosomal protein S6 kinase B1 (RPS6KB1) up-regulation to promote cell proliferation and differentiation, meanwhile negatively correlating with Bcl2 associated agonist of cell death (BAD) protein to inhibit apoptosis in CRC progression. Overall, our study provides a strong clinical evidence and molecular mechanism to support that CXCL8 plays an important role in the occurrence and development of CRC.